(untitled) (Journal of Governance and Development (JGD), 2015)
Fisher communities are a homogenous community with close relationships. These close relationships are recognised as bonding social capital. At the same time, they have relationships with other groups of people identified as linking social capital, in which an authority group has direct influence on fishermen. Two types of social capital influence the lives of fishermen but they always confront issues of fragility and the effort to expand those relationships. To investigate the issues, this article focuses on possession, fragility and capacity building of bonding and linking social capital amongst fishermen. The research involved 100 fishermen residing in Kuala Terengganu. The data were analysed based on descriptive, multiple regression and Pearson Correlation statistical procedures. The findings confirm a significant relationship among possession, fragility and capacity building of bonding social capital. However the fragility of bonding social capital is more influential on bonding social capital possession. Therefore bonding social capital will likely be vulnerable if fragility of social capital remains at a specific level. Thus, effort to strengthen bonding social capital must be made consistently. For linking social capital, the level and capital capacity building of relationships between fishermen and authority groups are at a low level. Efforts to increase this type of social capital must be given attention by fishermen.